2019
DOI: 10.1038/s41386-019-0398-4
|View full text |Cite
|
Sign up to set email alerts
|

Kappa-opioid receptors, dynorphin, and cocaine addiction: a positron emission tomography study

Abstract: Animal studies indicate that the kappa-opioid receptor/dynorphin system plays an important role in cocaine binges and stressinduced relapse. Our goal was to investigate changes in kappa-opioid receptor (KOR) availability in the human brain using positron emission tomography (PET), before and after a cocaine binge. We also investigated the correlation between KOR and stress-induced cocaine self-administration. PET imaging was performed with the KOR selective agonist [ 11 C]GR103545. Subjects with cocaine-use di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Although not specific to OUD, the findings from human positron-emission tomography (PET) imaging studies have found associations between endogenous opioid function, and subjective and behavioral responses to both drugs of abuse and pain. For example, k-opioid receptor availability is associated with stress-induced cocaine self-administration in subjects with cocaine-use disorder [ 279 ], altered vs. binding potential for the µ-receptor agonist [ 11 C]carfentanil is associated with alcohol craving and relapse risk in abstinent alcoholics [ 280 , 281 , 282 ], the µ-receptor binding potential correlates with nicotine dependence and reward in smokers [ 283 ], and alterations in endogenous opioids and µ-receptors in patients with chronic nonspecific back pain are associated with both sensory and affective elements of the pain experience [ 284 ]. To date, we are not aware of any neuroimaging studies that have evaluated the effects of ELS on opioid neurotransmission in humans or any controlled human laboratory studies that have examined ELS contribution to human opioid sensitivity.…”
Section: Role Of Endogenous Opioid Neurotransmitter System In Els and Oudmentioning
confidence: 99%
“…Although not specific to OUD, the findings from human positron-emission tomography (PET) imaging studies have found associations between endogenous opioid function, and subjective and behavioral responses to both drugs of abuse and pain. For example, k-opioid receptor availability is associated with stress-induced cocaine self-administration in subjects with cocaine-use disorder [ 279 ], altered vs. binding potential for the µ-receptor agonist [ 11 C]carfentanil is associated with alcohol craving and relapse risk in abstinent alcoholics [ 280 , 281 , 282 ], the µ-receptor binding potential correlates with nicotine dependence and reward in smokers [ 283 ], and alterations in endogenous opioids and µ-receptors in patients with chronic nonspecific back pain are associated with both sensory and affective elements of the pain experience [ 284 ]. To date, we are not aware of any neuroimaging studies that have evaluated the effects of ELS on opioid neurotransmission in humans or any controlled human laboratory studies that have examined ELS contribution to human opioid sensitivity.…”
Section: Role Of Endogenous Opioid Neurotransmitter System In Els and Oudmentioning
confidence: 99%
“…Just for example, κORs have an established role in the reinstatement of stress induced drug use in experimental animals, i.e. nicotine use [229], and very recent results indicate a relationship between κORs and stress-induced binge cocaine use [197].…”
Section: Discussionmentioning
confidence: 99%
“…Binge cocaine users showed a significant association between [ 11 C]GR103545 ( 25 ) binding to κORs with the amount of drug consumed. Furthermore, a three-day cocaine binge reduced binding by about 15% [197]. The cerebral binding (V T ) of the ORL1 ligand [ 11 C]NOP-1A ( 36 ) was globally elevated 10% in detoxified cocaine users [198].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The Dyn/KOR system is distributed throughout different brain regions, with KORs expressed in various types of mood-related neurons including serotonergic neurons ( Land et al, 2009 ), corticotropin-releasing factor (CRF) neurons ( Marchant et al, 2007 ), and DA neurons ( Liu et al, 2019 ; Figure 1 ). It is widely accepted that KOR activation produces negative affect, both in human beings and in rodents ( Martinez et al, 2019 ). Moreover, ablation of KORs from DA neurons or basolateral amygdala (BLA) glutamatergic terminals in the medial prefrontal cortex produces an anxiolytic phenotype ( Margolis et al, 2006 ; Lowery-Gionta et al, 2018 ), suggesting that the KOR system is critical for the expression of negative affect.…”
Section: Kor Expression and Signalingmentioning
confidence: 99%